ANALISIS POLA KORELASI HARGA DAN VOLUME SAHAM BBCA MENGGUNAKAN ALGORITMA APRIORI - Noviyanto Firmansyah, Heru; Alwani, Yazid; Henandra Eka Putra, Dias; Verdinand, Rhenal; Arifin, Muhammad (Universitas Majalengka, 2025)
This study will determine the stock movement pattern of PT Bank Central Asia Tbk (BBCA) using Association Rule Mining according to the Apriori algorithm. The main focus is to investigate the correlation of the lowest price, the highest price, and the trading volume of BBCA shares in one time period. Past stock data is first processed and discretized into categorical data: lowest and highest, on each attribute. The data mining process is carried out using WEKA software to generate association rules with very high confidence values and lift values. Mining produces the top 10 association rules, some of which have 100% confidence values and lift values greater than 1, indicating a very strong relationship between the attributes. For example, it is found that when the lowest price is in the